The phenology of Epilobium hirsutum L.: assessing marker compounds variability of a pharmaceutically important plant remedy - Olha Mykhailenko; Olha Mykhailenko; Olha Mykhailenko; Banaz Jalil; Kateryna Uminska; Liudas Ivanauskas; Zigmantas Gudžinskas; Michael Heinrich; Michael Heinrich (Frontiers in Pharmacology)
BackgroundEpilobium hirsutum L. (Onagraceae), a perennial medicinal plant, has considerable pharmaceutical value due to its phenolic acids, flavonoids, and ellagitannins, including oenothein A and B. The plant is reported to have therapeutic benefits for several conditions, such as prostate gland, bladder, and hormonal disorders. This study aimed to provide evidence-based data on the chemical composition of the species over a 1-year cycle and define the optimal harvesting period, which is essential to ensure consistency and efficacy in plant-derived products.MethodsThe phytochemical variability of E. hirsutum across habitats (mesic grassland, wet grassland, and lake shore), plant parts (leaves and stems), and phenological stages (from April to October) was investigated. Using HPLC and HPTLC methods, 11 pharmacologically active marker compounds were quantified in 78 samples collected every 2 weeks during 2023.ResultsAmong the hydroxycinnamic acids, chlorogenic acid was dominant in samples from shaded habitats, with maximum accumulation in samples from leaves during the vegetative phase (up to 2.25 mg/g DW). Flavonoids such as isoquercitrin and hyperoside peaked in leaves from the lake shore and wet grassland habitats during flowering. Oenothein B, a major ellagitannin, showed the highest concentrations in wet grassland leaves during flowering (73.97 mg/g DW).ConclusionThis study is the first to integrate habitat, phenology, and plant part data to characterise seasonal dynamics of key marker compounds in E. hirsutum under natural east-part of the United Kingdom conditions. Shaded, moist habitats were found to promote higher biosynthesis of secondary metabolites, whereas open, dry conditions favoured biomass yield. Distinct seasonal patterns in the accumulation of β-hydroxycinnamic acids and ellagitannins provide insight into their physiological functions and potential pharmacological significance. By identifying the dynamics of marker compounds and optimal harvesting periods, the study provides a framework for sustainable industrial practices for pharmaceutical raw material production and supports standardisation in herbal production.